Data and applications security and privacy XXXIII : 33rd Annual IFIP WG 11.3 Conferences, DBSec 2019, Charleston, SC, USA, July 15-17, 2019, proceedings /: 33rd Annual IFIP WG 11.3 Conferences, DBSec 2019, Charleston, SC, USA, July 15-17, 2019, proceedings. ([2019]) - Unknown
No abstract available